LAW ENFORCEMENT AGAINST PERPETRATORS OF CRIMINAL OFFENSES OF MOTORCYCLE EMBEZZLEMENT UNDER DECISION NO. 85/PID.B/2022/PN KTG - Carlos, Christcarsel Brandlay Theolvano; Subekti, Subekti; Borman, M. Syahrul; Suyono, Yoyok Ucuk; Prawesthi, Wahyu (jfpublisher, 2023)
The development of an advanced era does not eliminate the possibility that the modus operandi of criminal acts is also increasingly developed, both in thought and technology. These developments affect various individuals to do various ways to fulfill their desires by doing everything that has an impact on someone later. The most dominant crime case is the type of crime against property, that is, embezzlement. Crimes reported by the public to Kotamobagu Police continue to increase. One of these crimes is the crime of motorcycle embezzlement. The objective of this research is to find out the law enforcement against the perpetrators of motorcycle embezzlement under Decision No. 85/Pid.B/2022/PN Ktg. This research uses a case approach to examine the application of legal norms committed in legal practice, especially regarding cases that have been decided, and a statutory approach by examining all laws and regulations related to the legal issues being addressed. Based on the research results, in this case, the suspect will be charged with the criminal offense of motorcycle embezzlement as referred to in Article 372 of the Criminal Code with a maximum imprisonment of four years. In addition, the crime of embezzlement is a criminal offense that cannot be avoided.